(In)visibilité des classes pauvres en ville par le prisme des cortiços paulistes au Brésil - Octavie Paris (Confins)
Referring to the Brazilian poorest classes housing topic, the automatism frequently is to think about the favela, urban image which belongs to the Brazilian urban landscape settled in the collective imaginary (or created by Medias and political discourses). Far from saying that the issues about the favela’s topic have been exhaustively studied by social science research, it seems interesting to study others popular modes of living which are present in large Brazilian cities, among them, the cortiço one. This article will try to propose, not a precise and finished cortiço’s definition [too hard to do for various reasons] but rather a presentation of this housing by the cortiços’ study of a central neighborhood of São Paulo city: Bela Vista. After the cortiço’s urban reality contextualization, will be underlined, with two steps : its “invisibility” both at the building, in the physical sense so, of its inscription in the city urban landscape and at lesser scale in the neighborhood landscape, both at the figurative sense by the own cortiço’s economy organization. For this purpose, the notion of “regime of visibility” will be borrowed to Lévy and Lussault, enhancing the specificities of this mode of housing that is the cortiço.